Value-based production planning in non-ferrous metal industries: Application in the copper industry. (2nd October 2020) - Siemon, Michel; Schiffer, Maximilian; Mitra, Sumit; Walther, Grit
Abstract: Production planners in the non-ferrous metal industry face an inherent combinatorial complexity of the metal production process within a fast-changing market environment. Herein, we study the benefit of an integrated optimization-based planning approach. We present the first value-based optimization approach for operational planning in the non-ferrous metal industry that yields high economic and technical benefits. We present a mixed-integer linear program for non-ferrous metal operational production planning that covers the complexity of material flows and the entire production process and is amenable for real-time application. We give insights into the practical implementation and evaluation of our modeling approach at a plant of Aurubis, a large European non-ferrous metal producer. Our results show that an optimization and value-based production planning approach provides significant benefits, including a 38% better planning solution in practice. In addition to economic benefits, we highlight the technical advantages that result from a detailed techno-economic representation of the entire production process.